The effect of fertilizers on the biochemical composition of blueberies fruits on the high cutover peatland - Rupasova, Zhanna A.; Yakovlev, Alexander P.; Vasilevskaya, Tamara I.; Krinitskaya, Natalia B.; Yaroshuk, Andrey A.; Karbanovich, Tatiana M.; Goncharova, Lyudmila V.; Kolomiets, Emilia I.; Aleschenkova, Zinaida M. (Journal of the Belarusian State University. Ecology, 2019)
The results are presented of comparative study of biochemical composition of fruits V. angustifolium and half-high-bush blueberry Northcountry and Northblue at fertilizer application NPK-compound (N16Р16К16) and of some microbial specimen – a liquid product of MaKlor in concentration of 10 and 50 %, a liquid and dry product of Agromik, and also a liquid product of Baktopin at the differentiated and joint application in test crop on recultivated cutover peatlands. On the background of the weather conditions of the vegetation period close to the average long-term norm, the tested agro-techniques contributed to a significant transformation of the biochemical composition of blueberry fruits. It consisted in the improvement of their taste properties due to the enhancement of the biosynthesis of soluble sugars with the inhibition of that of organic acids, as well as in their depletion of C- and P-vitamins, the most significant when making N16P16K16. In the conditions of the hot and dry season for all taxa of blueberry, especially for interspecific hybrids, the positive influence of microbial fertilizers on the quality of fruits has been shown. At the same time, V. angustifolium showed an increase in the integral level of their nutritional and vitamin value 1.3–2.5 times as compared to the control, most significant on the background of the introduction of a 50 % solution of the drug MaCloR, as well as its 10% solution in combination with AMG. In a varietal blueberry with an increase of this indicator in 2.5–14 times the most effective was the joint application of the drug Baktopin in combination with AMG dry mycorrhizal fertilizer.